Implementing circularity within the apparel industry in the Eu - analyzing barriers to circularity and investigating the role consumers play in overcoming or reinforcing them - Costa, Carolina Alexandra Mendes da (2022)
This paper assesses the practicality and likelihood of implementing circularity within the European apparel market. When analyzing potential barriers to circularity, it becomes evident that there are three major forces de- and accelerating progress: The public sector, the private sector, and consumers. Upon critically assessing the roles these play in this transition towards circularity, it was found that despite there being many hurdles to overcome for each, the most significant one is likely to stem from the interconnectedness of the roles. Particularly among consumers, results showed an attitude-behavior gap between their willingness to engage in circular practices and their actual engagement.